Nurbs continuity: Applications in architecture, product and digital fabrication - Del Blanco García, Federico; García Ríos, Ismael; González Uriel, Ana; Fernández Cabo, Miguel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The increasing complexity in contemporary architectural design has given rise to free-form surfaces that cannot be solved by traditional design and construction methods. The study of the continuity of NURBS surfaces and curves becomes especially relevant, either to segment a complex surface in fragments that allow its rationalization, or for the design through the aggregation of several surfaces looking for the uniformity of the whole. Different methods of establishing continuity between NURBS are analyzed, taking into account the different parameters that define the NURBS and their influence on the level of smoothness and deviation obtained.